Monetary union for the development process in the East African community: business cycle synchronization approach - Ahmed Sheikh, Kamaludin; Nurul Azam, Mohammad; Rabby, Talukder Golam; Alam, Gazi Mahabubul; Khan, Issa (Academic Journals, 2011)
This paper empirically examines the suitability of monetary union in East African community members namely, Burundi, Kenya, Rwanda, Tanzania and Uganda, on the basis of business cycle synchronization. This research considers annual GDP (gross domestic product) data from IMF (international monetary fund) for the period of 1980 to 2010. In order to extract the business cycles and trends, the study uses HP (Hodrick-Prescott) and the BP (band pass) filters. After identifying the cycles and trends of the business cycle, the study considers cross country correlation analysis and analysis of variance technique to examine whether EAC (East African community) countries are characterized by synchronized business cycles or not. The results show that four EAC countries (Burundi, Kenya, Tanzania and Uganda) among five countries are having similar pattern of business cycle and trend from the last ten years of the formation of the EAC. The research concludes that these countries, except Rwanda, do not differ significantly in transitory or cycle components but do differ in permanent components especially in growth trend.